Pemberdayaan Masyarakat Non-Produktif Melalui Keterampilan Pembuatan Ecobrick - Eka Herlina; Muhammad Fathurrahman; Leny Heliawati; Ade Heri Mulyati; Siti Fatimah; Abyan Jausan Kabir (Jurnal Pemberdayaan Masyarakat, 2024)
The non-productive community that we are partners with is Bina Dakwah Middle School in Leuwiliang Village, Bogor Regency. This institution is an educational institution that is developing and still lacks finances and skills. The aim of this service activity is to provide skills for making ecobrick products with the hope of being able to lift people to work and become productive people so that they can improve economic welfare. The method used in this service activity is a participatory method, namely by means of counseling and direct practice. The outreach began with program outreach, outreach on plastic waste management, outreach and training on the practice of making ecobricks as well as outreach on creating an online marketing network. The result of this activity was an increase in partners' knowledge and insight regarding plastic waste management, and partners succeeded in making ecobrick chair products.